Single photon double ionization of Helium at 800 eV – observation of the Quasi Free Mechanism - Schöffler, M. S.; Jahnke, T.; Waitz, M.; Trinter, F.; Lenz, U.; Stuck, C.; Jones, M.; Pindzola, M. S.; Belkacem, A.; Cocke, C. L.; Landers, A.; Colgan, J.; et al. (My University, 2014)
In a kinematically complete experiment we have measured the photo double ionization of Helium at a photon energy of 800 eV and observed He2+ ions with 0 momentum, corresponding to a back-to-back-emission of the two electrons. The results are in good agreement with theoretical calculations.